Use of amantadine in traumatic brain injury: an updated meta-analysis of randomized controlled trials - Félix, João; Araújo, Luísa; Henriques, Antônio; Pereira, Ana; Carneiro, Saul (Frontiers in Neurology, 2025)
IntroductionAmantadine has been shown to accelerate cognitive and functional brain recovery after cerebrovascular accidents. However, the efficacy of this drug in TBI patients remains poorly defined.MethodsWe performed a systematic review and meta-analysis of randomized trials (RCTs) evaluating the effects of amantadine in TBI patients. The Cochrane, Embase, and PubMed databases were systematically searched for trials published up to March 24, 2024. Data from previous RCTs were extracted and quality assessed according to Cochrane recommendations. Means and standard deviations with 95% confidence intervals were aggregated across studies. The primary outcomes assessed were Glasgow Coma Scale (GCS), Mini Mental State Examination (MMSE) and the Disability Rating Scale (DRS).ResultsFrom 1,292 database results, 6 studies with 426 patients were included, of which 205 received amantadine (48.12%). The Glasgow Coma Scale score on day 7 (MD 1.50; 95% CI 0.08–2.92; p = 0.038; I2 = 68%) was significantly higher in patients treated with amantadine than those treated with placebo. The Mini Mental State Examination (MD 3.23; 95% CI 0.53–5.94; p = 0.019; I2 = 0%) was also better in patients treated with amantadine. No significant differences in Disability Rating Scale, day 3 GCS, Glasgow Outcome Scale (GOS), length of hospital stay, or duration of mechanical ventilation were observed between amantadine and placebo groups.ConclusionIn our analysis, TBI patients benefit from the use of amantadine in the day 7 GCS score and show better results in the MMSE test, but placebo patients benefit from not using amantadine in the DRS between weeks 3 and 4. No other statistically significant results were found related to the use of this medication.Systematic review registration: https://www.crd.york.ac.uk/prospero/display_ record.php?ID=CRD42024538110, CRD42024538110.